Plant data survey in Porto Santo (Madeira Archipelago, Portugal): an update - Fontinha, Susana (2020)
The present contribution updates BORGES et al. (2008)’s “A list of the terrestrial fungi, flora and fauna of Madeira and Selvagens archipelagos”. Since then, and until the summer of 2019, 131 new taxa were cited, namely 30 bryophytes, one pteridophyte and 100 spermatophytes. Based on the compilation of written and unpublished information about the diversity of terrestrial plants cited for Porto Santo, the present work lists 696 taxa, including 134 bryophytes, 13 pteridophytes and 549 spermatophytes. Two species of mosses, Sematophyllum substrumulosum (Hampe) E. Britton and Tortula lanceolata R. H. Zander are recorded for the first time from Porto Santo, corresponding to material collected in 2018. Additionally, 12 species of spermatophytes, all cultivated, are referred for the first time to the island. Two species of pteridophytes, Ophioglossum lusitanicum L. and Hymenophyllum wilsonii Hook are proposed to be considered extinct.